Power System Harmonics Analysis, Effects and Mitigation Solutions for Power Quality Improvement - Zobaa, Ahmed; Abdel Aleem, Shady H. E.; Erhan Balci, Murat (IntechOpen, 2018)
Excessive utilization of power electronic devices and the increasing integration of renewable energy resources with their inverter-based interfaces into distribution systems have brought different power quality problems in these systems. There is no doubt that the transition from traditional centralized power systems to future decentralized smart grid necessities is paying much attention to power quality knowledge to realize better system reliability and performance to be ready for the big change in the coming years of accommodating thousands of decentralized generation units. This book aims to present harmonic modeling, analysis, and mitigation techniques for modern power systems. It is a tool for the practicing engineers of electrical power systems that are concerned with the power system harmonics. Likewise, it is a key resource for academics and researchers who have some background in electrical power systems.